Biocatalytic Process Optimization (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Biocatalysis is very appealing to the industry because it allows, in principle, the synthesis of products not accessible by chemical synthesis. Enzymes are very eﬀective, as are precise biocatalysts, as they are enantioselective, with mild reaction conditions and green chemistry. Biocatalysis is currently widely used in the pharmaceutical industry, food industry, cosmetic industry, and textile industry. This includes enzyme production, biocatalytic process development, biotransformation, enzyme engineering, immobilization, the synthesis of fine chemicals and the recycling of biocatalysts. One of the most challenging problems in biocatalysis applications is process optimization. This Special Issue shows that an optimized biocatalysis process can provide an environmentally friendly, clean, highly eﬃcient, low cost, and renewable process for the synthesis and production of valuable products. With further development and improvements, more biocatalysis processes may be applied in the future.